Answer:
(1,2)
Step-by-step explanation:
Substitution:
x + 2y = 5 Solve for x
x = -2y + 5 Substitute -2y + 5 in for x in the second equation
4x - 12y = -20
4(-2y + 5) - 12y = -20 Distribute the 4
-8y + 20 - 12 y = -20 Combine the y term
-20y + 20 = -20 Subtract 20 from both sides
-20y = -40 Divide both sides by -20
y = 2
Plug y into either of the 2 original equations to get x.
x + 2y = 5
x + 2(2) = 5
x + 4 = 5
x = 1
The answer is (2,1).
Elimination:
x + 2y = 5 4x - 12y = -20. We want to eliminate with the x or the y. I am going to eliminate the x's that means that I have to multiply the first equation all the way through by -4
(-4)(x + 2y) = (5) (-4) That makes the equivalent expression
-4x - 8y = -20 I will add that to 4x - 12y = -20
<u>4x - 12y = -20</u>
0x -20y = -40
-20y = -40
y = 2. Plug 2 into either the 2 original equation to find x. This time I will select the second original equation to find x.
4x -12y = -20
4x - 12(2) = -20
4x - 24 = -20
4x = 4
x = 1
Answer:
Step-by-step explanation:
You can simplify this by collecting the like terms. The only like terms are the pair 2x and 18 x
2x-18x = -16x
Now, put them back together,
-16x + 14y-19
Because Line 1 is parallel to Line 2, angle "a" should also be 46 degrees. b is complementary so it would be 180-46=134(degrees).
Any object when rotated by 360°, will look exactly the same
Answer:
Step-by-step explanation: